Transformation of Cultural Values in The Novel Di Bawah Langit yang Sama by Helga Rif (Literary Anthropology Approach) - Asep Ricky Subagya; Sri Suhita (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
This study aims to obtain information about transformation of the cultural value in the novel titled Di Bawah Langit yang Sama by Helga Rif. This research use qualitative descriptive method based on anthropology of literature approach. This research was conducted from January to July 2019. In this study, there is a focus that is studied, which is the form transformation of cultural values, while the study's sub-focus includes (1) preservation cultural values ​​and (2) revolution in cultural values. As for identifying and raising anthropological features in the novel using Koentjaraningrat theory which includes (1) human life equipment, (2) occupation, (3) social system, (4) language system, (5) arts, (6) knowledge system, and (7) religious system. In the novel entitled Di Bawah Langit yang Sama had been found the elements of transformation of cultural values ​​as much 103 data. Preservation of cultural values are 75 data, meanwhile the changes in the cultural values are 28 data. The most dominant data on maintaining cultural values ​​is an element of human life equipment and social systems. Meanwhile, the most dominant data on changes in cultural value is an element of the social system. The results of this study have implications for 2013 Learning Curriculum 2013 Revision 2018 in grade XII, KD 3.8 interpret the author's view of life in novels that are read and KD 4.8, which presents the results of interpretation of the views of the author either verbal or scripted.